คุณภาพชีวิตการทำงานของแพทย์ใช้ทุน โรงพยาบาลมหาราชนครเชียงใหม่ - ศศิวิมล เอกมหาชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of the independent study “Quality of Work Life of Interns, Maharaj Nakorn Chiang Mai Hospital” were to investigate factors which affected interns’ quality of work life, and to discover the level of their work life quality, based on work life concept, which consists of 6 factors: body, mind, social relations, environment, spirituality, and career stability. In this study, the data was collected by questionnaire distributed to 184 interns at Maharaj Nakorn Chiang Mai Hospital. The collected data was analyzed by descriptive statistics, namely frequency, percentage, mean, T-test and One-way ANOVA, LSD, including correlation analysis and multiple regression analysis. The results showed that the interns at Maharaj Nakorn Chiang Mai Hospital ranked the overall quality of work life at the medium level, and the 6 factors of quality of work life were ranked at the medium level. The interns ranked factors that affected their work life quality at the high level, in the following order: social relations, mind, spirituality, environment, career stability, and body. The correlation analysis showed that body, mind, social relations, environment, spirituality, and career stability linked with of quality of work life, and all of them were in the same direction. Multiple regression analysis showed the positive variation (R = 0.603), with body, environment, and spirituality significantly affecting the overall quality of work life.